Evolução e vulnerabilidade das falésias na costa leste do Ceará-Nordeste do Brasil - Silva, Rhaiane Rodrigues da (2022)
The cliffs are geomorphological features with a flat top and steep slopes present in the coastal zone of the world, varying their composition in rocky, limestone, ice and sedimentary. Coastal sedimentary cliffs are present on the Brazilian coast associated with the Barreiras Formation. With climate change, the processes of erosion of cliffs and reports of landslides near urban areas are becoming more recurrent. With this, the work aims to fill gaps regarding the geological and sedimentological characteristics of the cliffs, map the points that present greater vulnerabilities to high energy events and make predictions for the future, presenting pioneering data and a replicable methodology. With the hypothesis that the Ceará cliffs have a distinct lithology from the Barreiras Formation, of Miocene origin, they are sandier and more vulnerable in places where there is a greater movement of users. For this, 3D LiDAR images were used, collection of sedimentary samples from the cliffs for granulometric, geochemical (X-ray fluorescence) and chronological (Optically Stimulated Luminescence - OSL) analysis, in three significant beaches from the point of view of use and occupation in the east Ceará (Morro Branco, Canoa Quebrada and Icapuí). The results were divided into 3 parts in scientific article formats, the first being published in the Geosciences journal in 2020 and the other two in the process of being finalized and submitted to international journals, so the last one is written in English. The results show that 40% of the east coast of Ceará is composed of active cliffs and sandy clayey paleocliffs with poorly selected sediments and geochemical composition of silicon (72%), aluminum (13%), potassium (6%) and iron (3%), indicating terrigenous origin and fluvial deposition in a warmer glacial period with sea level 20m below the current one (ICM 5c). This deposition occurred between 49,000 ± 3,260 years and 95,850 ± 5,500 years before the present, and according to the chronology, they fall within the Marine Isotopic Stages 3 and 5c. In addition, in them we observed morphological features that indicate surface runoff (gullies), lithological and neotectonics differences (stepped surface) and strong subarea erosion (remounting erosion), in addition to marine erosion rates in 5% of the study area exceeding 1 m/yr and in 13%, between 0.24 and 1 m/yr. This is due to their erosive potential in the face of met oceanographic factors, so the active sandy cliffs presented 80% of high or very high vulnerability, highlighting four erosive hotspots on the beaches of Pontal de Maceió, Canoa Quebrada, Majorlândia and Retirinho. These points are highlighted for the decision-making of local coastal management, attention of the public authorities, avoiding serious accidents and for students and the scientific community to follow and deepen studies on the subject.